A Prospective Study of Surgical Site Infections in a Medical College Hospital - Ajeet Kumar; Bhartendu Kumar; Sunil Kumar (Asian Journal of Medical Research, 2020)
Background: Surgical site infections (SSI) are an important post-operative complication. Knowledge about its risk factors is essential. The present study was conducted to find the profile of surgical site infection among patients admitted in surgical ward of SKMCH, Muzaffarpur.Subjects and Methods:The present cross-sectional study included 322 patients undergoing surgery. Clinical details, onset of SSI and microbiological profile were noted.Results:Mean age of the cases was 43.7 years. 61.2% of these were males. 11.8% of the cases suffered from surgical site infection. Of the emergency surgeries, 20.2% had SSI while 8.1% elective surgery cases had SSI. 36.1% of the cases with dirty wound had SSI while only 5.2% of the cases with clean wound had such infection. S. aureus was the most common organism isolated (57.9%) followed by Pseudomonas (39.5%) and Klebsiella (23.7%).Conclusion: Incidence of SSI is higher in cases of emergency surgery and in dirty wounds.